Novel occurrence of Acute Ischaemic Stroke and DVT simultaneously in a patient of Scrub Typhus: A Case report - Chowdhury, Sampurna; Mukherjee, Rishav; Sinha, Pradip Kumar (Asian Journal of Medical Sciences, 2020)
Orientia tsutsugumashi ( erstwhile Rickettsia tsutsugumashi) is an obligate intracellular bacteria that is showing re-emergence in the last decade in eastern India 1-3. Commonly it causes acute febrile illness with rash and multiple organ involvement including CNS - In fact, Scrub encephalopathy has become a common cause of AES in recent times. Although pathogenesis of Scrub typhus is still uncertain, research on other Rickettsiales suggest infection of endothelial cells and vascular dysfunction to be the main mechanism. Based on that pathology we report two very rare manifestations - Acute Ischaemic Stroke and DVT in a single patient of Scrub typhus, occurring simultaneously. No such simultaneous occurrence has been reported in literature till date.